2020
DOI: 10.1007/s12630-020-01816-z
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with critically ill patients with COVID-19 in Montreal

Abstract: Purpose Montreal has been the epicentre of the coronavirus disease (COVID-19) pandemic in Canada. Given the regional disparities in incidence and mortality in the general population, we aimed to describe local characteristics, treatments, and outcomes of critically ill COVID-19 patients in Montreal. Methods A single-centre retrospective cohort of consecutive adult patients admitted to the intensive care unit (ICU) of Hôpital du Sacre´-Coeur de Montre´al with confirmed COVID-19 were included. Results Between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
2
19
0
7
Order By: Relevance
“…Among patients admitted to the ICU for COVID-19, we found that about two-thirds of patients received invasive mechanical ventilation and one-quarter died, which is similar to the results of 2 small Canadian ICU studies. 6,7 We extend this literature by including patients who did not require admission to the ICU, finding that about one-quarter of all patients admitted to hospital for COVID-19, and one-fifth of those admitted through the emergency department, used the ICU. In the global context, patients with COVID-19 in Ontario (median age 65 yr) were somewhat older than patients in China (median 51-56 yr) 5,46 and the US (median 62-63 yr), [1][2][3] and were younger than those in the UK (median 73 yr), 4 but mortality and ICU use were generally similar.…”
Section: Discussionmentioning
confidence: 88%
“…Among patients admitted to the ICU for COVID-19, we found that about two-thirds of patients received invasive mechanical ventilation and one-quarter died, which is similar to the results of 2 small Canadian ICU studies. 6,7 We extend this literature by including patients who did not require admission to the ICU, finding that about one-quarter of all patients admitted to hospital for COVID-19, and one-fifth of those admitted through the emergency department, used the ICU. In the global context, patients with COVID-19 in Ontario (median age 65 yr) were somewhat older than patients in China (median 51-56 yr) 5,46 and the US (median 62-63 yr), [1][2][3] and were younger than those in the UK (median 73 yr), 4 but mortality and ICU use were generally similar.…”
Section: Discussionmentioning
confidence: 88%
“…Acredita-se que os principais mecanismos responsáveis pela gravidade nesses pacientes estão relacionados com a liberação exacerbada de mediadores inflamatórios e a desregulação do sistema de coagulação, o que favorece o desenvolvimento da SRAG e predispõe à necessidade de suporte respiratório, além da instabilidade clínica e hemodinâmica 2 .…”
Section: Introductionunclassified
“…Em função da gravidade dos pacientes acometidos, do aumento exorbitante de internações hospitalares, aumento na demanda de suporte respiratório invasivo, aumento do tempo de internação hospitalar e a necessidade de múltiplos dispositivos e terapêuticas para a recuperação desses pacientes 1,2 , os serviços de saúde sentiram-se pressionados, os custos aumentaram demasiadamente e houve sobrecarga de trabalho das equipes de saúde, caracterizando um panorama mundial quase caótico.…”
Section: Introductionunclassified
“…We performed a MEDLINE search from inception to 3 January 2021 using the following keywords: ‘COVID-19’, ‘Intensive Care’ and ‘Canada’, and found three observational studies describing COVID-19 ICU outcomes in Canada [ [2] , [3] , [4] ]. The studies were published between May and November 2020, describe patients in Canada during the first wave of the Canadian COVID-19 pandemic, and satisfy all of the authors inclusion criteria.…”
mentioning
confidence: 99%
“…[ 2 ] Cavayas et al. [ 3 ] Yang et al. [ 4 ] Age (years) 69 62 66 Male 79 (68%) 50 (67%) 64 (60%) Sample size 117 75 106 NIV 15 (13%) 16 (21%) 0 (0%) HFNO 43 (37%) 2 (3%) 51 (48%) IMV 74 (63%) 43 (57%) 65 (61%) ECMO 3 (3%) 1 (1%) 0 (0%) RRT 16 (14%) 7 (9%) 12 (11%) Vasopressors 65 (56%) NA NA ICU LOS (days) 9 10 10 ICU mortality 18 (15%) 17 (23%) 18 (17%) ICU mortality if IMV used 15 (20%) 8 (19%) 12 (19%) Hospital mortality 30 (26%) 19 (25%) 21 (20%) Abbreviations: COVID-19, coronavirus disease 2019; ECMO, extracorporeal membrane oxygenation; HFNO, high-flow nasal oxygen; IMV, invasive mechanical ventilation; LOS, length of stay; NIV, non-invasive ventilation; RRT, renal replacement therapy.…”
mentioning
confidence: 99%